Pengukuran Tinggi Sebenarnya Objek pada Foto Digital Menggunakan Euclidean Distance - Rakhmad Kuswandhie; Jufriadif Na’am; Yuhandri Yuhandri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Digital photos are generated from the camera. In the photo there are some object that can be observed. The object in images is a representation of the fact that in the real world. The size of an object in a digital image can represent the true size of an image object with a certain size scale. The actual size of the object in the photo can not be known directly. Digital photos used in the research is the image generated from the camera phone with 8MB resolution and the distance of the camera to photo objects as far as 1, 3 and 5 meters with 3 different objects, ie gallons, chairs and legs. The size of objects in a digital image will be measured using an application created with the C # programming language. Measuring objects in photos using Euclidean Distance. Next is calculated the actual size of the object that is in the photo by using trigonometric function. The test result of 3 objects on digital photos with 3 different distances obtained the actual object size with an accuracy are 99,993%.